Association of Objectively Measured Physical Activity and Metabolic Syndrome among U.S. Adults with Osteoarthritis - Liu, Shao-Hsien (Arthritis Care Res (Hoboken), 2015)
OBJECTIVE: To investigate the association between objectively-measured physical activity and metabolic syndrome among adults with osteoarthritis (OA). METHODS: Using cross-sectional data from 2003–2006 NHANES, we identified 566 adults with OA with available accelerometer data assessed using Actigraph AM-7164 and measurements necessary to determine metabolic syndrome by Adult Treatment Panel III. Analysis of variance was conducted to examine the association between continuous variables in each activity level and metabolic syndrome components. Logistic models estimated the relationship of quartile of daily minutes of different physical activity levels to odds of metabolic syndrome adjusted for socioeconomic and health factors. RESULTS: Among persons with OA, most were female with average age 62.1 years and average duration of disease of 12.9 years. Half of adults with OA had metabolic syndrome (51.0%; 95% Confidence Interval (CI): 44.2% to 57.8%), and only 9.6% engaged in the recommended 150 minutes per week of moderate/vigorous physical activity. Total sedentary time was associated with higher rates of metabolic syndrome and its components while light and moderate/vigorous objectively-measured physical activity were inversely associated with metabolic syndrome and its components. Higher levels of light activity was associated with lower prevalence of metabolic syndrome (quartile 4 versus quartile 1: adjusted odds ratio: 0.45; 95% CI: 0.24 to 0.84; p-value for linear trend < 0.005). CONCLUSION: Most U.S. adults with OA are sedentary. Increased daily minutes in physical activity, especially in light intensity, is more likely to be associated with decreasing prevalence of metabolic syndrome among persons with OA.